Nonlinear responses in salt marsh functioning to increased nitrogen addition. Issue 4 (1st April 2015) - Vivanco, Lucía; Irvine, Irina C.; Martiny, Jennifer B. H.
Abstract : Salt marshes provide storm protection to shorelines, sequester carbon (C), and mitigate coastal eutrophication. These valuable coastal ecosystems are confronted with increasing nitrogen (N) inputs from anthropogenic sources, such as agricultural runoff, wastewater, and atmospheric deposition. To inform predictions of salt marsh functioning and sustainability in the future, we characterized the response of a variety of plant, microbial, and sediment responses to a seven‐level gradient of N addition in three Californian salt marshes after 7 and 14 months of N addition. The marshes showed variable responses to the experimental N gradient that can be grouped as neutral (root biomass, sediment respiration, potential carbon mineralization, and potential net nitrification), linear (increasing methane flux, decreasing potential net N mineralization, and increasing sediment inorganic N), and nonlinear (saturating aboveground plant biomass and leaf N content, and exponentially increasing sediment inorganic and organic N). The three salt marshes showed quantitative differences in most ecosystem properties and processes rates; however, the form of the response curves to N addition were generally consistent across the three marshes, indicating that the responses observed may be applicable to other marshes in the region. Only for sediment properties (inorganic and organic N pool) did the shape of the response differ significantly between marshes. Overall, the study suggests salt marshes are limited in their ability to sequester C and N with future increases in N, even without further losses in marsh area.